Crystal structure poly-(μ2-1-(4-(1H-imidazol-1-yl)benzyl)-1H-1,2,4-triazolyl-κ2NN1:N2N)-(μ3-2,2′-(1,2-phenylene)diacetato-κ5-O1,O2:O2:O3,O4)cadmium(II), C22H19CdN5O4 - Xin Ling-Yun (Zeitschrift für Kristallographie - New Crystal Structures, 2016)
C22H19CdN5O4, monoclinic, P21/c, a = 11.7546(16) Å, b = 19.769(3) Å, c = 9.5012(13) Å, β = 106.252(2)°, V = 2119.6(5) Å3, Z = 4, Rgt(F) = 0.0348, wRref(F2) = 0.0814, T = 296(2) K.